2008
DOI: 10.1111/j.1755-0998.2008.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite DNA toolkit for studying population structure in Apis mellifera

Abstract: We present a set of 18 microsatellite DNA markers that can be run in two multiplex polymerase chain reactions as standard tool for assessing molecular ecological problems in honeybees (Apis mellifera). In addition to a set of six unlinked loci testing for classical population genetic parameters, we present three sets of four tightly linked loci, each located on three different chromosomes. These linked markers are useful for determining the number of colonies in a population as well as the parentage of drones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 11 publications
1
66
0
2
Order By: Relevance
“…We subjected the four DNA extracts from each colony to PCR at 12 variable microsatellite loci: A24, A28, A79, A88, A107, Ap43, Ap66, Ap81, AC006, B124 (Estoup et al 1995;Garnery et al 1992;Solignac et al 2003), and HB-THE-03 and HB-THE-04 (Shaibi et al 2008), using the previously reported reaction conditions. The final reaction volume per sample was~10 μL and contained 5 μL of PCR Master Mix (Promega, Madison, WI), 1.0-2.5 μL of fluorescent dye-labeled primer, 0.9 μL of nuclease-free water, and 2 μL of DNA extract.…”
Section: Microsatellitesmentioning
confidence: 99%
“…We subjected the four DNA extracts from each colony to PCR at 12 variable microsatellite loci: A24, A28, A79, A88, A107, Ap43, Ap66, Ap81, AC006, B124 (Estoup et al 1995;Garnery et al 1992;Solignac et al 2003), and HB-THE-03 and HB-THE-04 (Shaibi et al 2008), using the previously reported reaction conditions. The final reaction volume per sample was~10 μL and contained 5 μL of PCR Master Mix (Promega, Madison, WI), 1.0-2.5 μL of fluorescent dye-labeled primer, 0.9 μL of nuclease-free water, and 2 μL of DNA extract.…”
Section: Microsatellitesmentioning
confidence: 99%
“…Drones in the DCAs were only matched to the hives if their haplotype matched perfectly that of the reconstructed hive queens, including those represented by few hive drones. Those that could not be positively allocated to hives were allocated to unknown queens outside the study, as described before (Shaibi et al 2008;Jaffé et al 2009). …”
Section: Queen Genotype Reconstruction and Drone Colony Assignmentmentioning
confidence: 99%
“…The DNA from each drone was extracted using a Chelex protocol (Walsh et al 1991). Three sets of four, tightly linked microsatellite markers were used to identify individual drone genotypes (Shaibi et al 2008). The three linkage groups are located on different chromosomes:…”
Section: Dna Extraction and Microsatellite Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the three linked marker sets of the standard microsatellite tool kit for studying honeybee populations (Shaibi et al 2008). These include two loci on chromosome 3 next to the sex locus (csd) spanning 11.6 kb or 0.2 cM (HB-SEX-01, HB-SEX-03).…”
Section: Dna Analysesmentioning
confidence: 99%